Design of the Muhammadiyah University of Madura Campus in Sampang Regency with Biophilic Architecture Approach - Rus Armi, Zaqi Islammaulana; Gunawan, Gunawan; Rofi'i, Rofi'i (Lakar: Jurnal Arsitektur, 2025)
The Muhammadiyah organization is the oldest Islamic organization that still exists in Indonesia with the "amar ma`ruf nahi munkar" da'wah movement. The Muhammadiyah organization has 5 fields of business charity, one of which is the business charity in the field of education. The Muhammadiyah organization on Madura Island has great aspirations for the establishment of Muhammadiyah Madura University as a form of realization of business charity in the field of education. The establishment of this campus has been consolidated since 2016 until 2021 and is planned to be built in Camplong District, Sampang Regency, on land owned by Muhammadiyah, covering an area of 50 hectares. However, the natural conditions in Sampang Regency are still quite concerning due to significant environmental degradation caused by the actions of its own people, making it essential to design solutions that can address these environmental issues. Therefore, the biofilic architecture approach can serve as the best foundational concept in the campus design as a solution to the environmental damage occurring in Sampang Regency. The application of the biophilic architecture approach to this design includes all categories of biophilic design principles, namely by bringing nature into the design, analogizing nature to buildings, and imitating the nature of natural spaces. The result of this paper is the design of the Muhammadiyah Madura University campus with a biophilic architecture approach as a form of realization of the ideals of the Muhammadiyah organization in the field of education without adding to the natural problems in Sampang Regency.